Acute respiratory infection. Factors influencing the need for prolonged medical care (Colombia Medica, 1993)
For this study, 336 children from O to 48 months from a low-income urban neighborhood in Cali, Colombia, were observed from birth by means of weekly home visits to detect cases of acute respiratory tract infections, as well as to study family and neighborhood characteristics that may influence the need to prolonged medical supervision. A trained physician at the clinic confirmed all suspected cases. 1000 episodes of low respiratory tract infections (LRTI) were documented. All of them received treatment and medical) supervision, and no mortality was observed. The following risk factors were positively associated with the need for prolonged medical] supervision: location of the kitchen within the house, fuel for cooking derived from gasoline, walls of the house made of mud and bamboo, and the house located in a street whose dimensions avoid the transit of automobiles.